A Área de Proteção Ambiental da Bacia do Rio São Bartolomeu na Política Nacional de Meio Ambiente : o caso da Comunidade Bananal e a ADI nº 2990/2003 - Martini, Elza Carolina Davi de Oliveira (2016)
This investigation comprises a legal study of the Environmental Protection Area (APA) of the São Bartolomeu River, created in 1983, before the landmark of the 1988 ’s Republican Constitution, which gave the territory a legal importance for protection and guarantee purposes for the conservation and preservation of natural resources in this Brazilian river basin, comprising much of the Federal District and surroundings, seeking to highlight the legal and dogmatic aspects of environmental protection and conservation areas, as well as its problems facing the delegation of management powers and supervision of this area under the Union to the Federal District, through the normative instrument provided by Federal Law No 9.262, enacted in 1996, seeking to identify the dogmatic and philosophical aspects relating to the judicial review of the constitutionality of this legislation, carried out before the Supreme Court through the direct action of unconstitutionality no 2990/2003. The inductive and analytical methods are used, considering a documentary and interdisciplinary research, in order to demonstrate how the exemption from bidding on federal public lands was object of non regulable urban land subdivisions, wich affects places like the northwest sector of the city of Brasilia, in which the Bananal Reserve is situated, whose reality will reveal the compromising of the well-being of human populations and environmental resources in the region, deconstructing the judicial case of public legal bidding waiver concerning the negotiation of areas in the basin and its environs, demonstrating with it the systemic retroflection aspects in which the Right is held in its clumsy appearance, lack of concern with the chosen means, as well as the axiological sense of environmental guardianship, in contrast with the judicial affirmation of a social interest that in fact does not exist, and therefore unable to deconstruct the requirement of public bidding regulated by Law no 8.666/1993.